Severe Acute Malnutrition Results in Lower Lumefantrine Exposure in Children Treated With Artemether‐Lumefantrine for Uncomplicated Malaria. Issue 6 (23rd July 2019) - Chotsiri, Palang; Denoeud‐Ndam, Lise; Baudin, Elisabeth; Guindo, Ousmane; Diawara, Halimatou; Attaher, Oumar; Smit, Michiel; Guerin, Philippe J.; Doumbo, Ogobara K.; Wiesner, Lubbe; Barnes, Karen I.; Hoglund, Richard M.; et al.
Abstract : Severe acute malnutrition (SAM) has been reported to be associated with increased malaria morbidity in Sub‐Saharan African children and may affect the pharmacology of antimalarial drugs. This population pharmacokinetic (PK)‐pharmacodynamic study included 131 SAM and 266 non‐SAM children administered artemether‐lumefantrine twice daily for 3 days. Lumefantrine capillary plasma concentrations were adequately described by two transit‐absorption compartments followed by two distribution compartments. Allometrically scaled body weight and an enzymatic maturation effect were included in the PK model. Mid‐upper arm circumference was associated with decreased absorption of lumefantrine (25.4% decreased absorption per 1 cm reduction). Risk of recurrent malaria episodes (i.e., reinfection) were characterized by an interval‐censored time‐to‐event model with a sigmoid maximum‐effect model describing the effect of lumefantrine. SAM children were at risk of underexposure to lumefantrine and an increased risk of malaria reinfection compared with well‐nourished children. Research on optimized regimens should be considered for malaria treatment in malnourished children.